Military justice a guide to the issues - Morris, Lawrence J. (Contemporary military, strategic, and security issues, 2010)
The goal of this book is to provide an overview of the theory and practice of military justice, so that the interested reader-- especially the nonlawyer, but also the practitioner new to military justice-- receives a thorough and balanced overview of the military justice system. The book provides a comprehensive treatment of the current military justice system, enriched by enough history to make current practices understandable and future changes foreseeable. It addresses the system from the standpoint of society, which invests in the military; the command, through which good order and discipline are administered; and those who participate in the trial process